Experimental study on nanoparticle injection by using a lab-scale wellbore system. (March 2022) - Li, Linfei; Zhang, Yige; Hubler, Mija H.; Xi, Yunping
Abstract: After long-term underground storage of CO2 gas, leakage generated from the cement annulus in the wellbore system is often detected due to unbalanced pressure, chemical attack, etc. In this paper, nanoparticle injection technology is introduced to inject different types of nanoparticles into the cementitious material for repairing the leakage paths through electrochemical means. The pressure vessel is designed and built to provide a realistic underground environment with high pressure and high temperature. The testing results are evaluated by the saturate-drying method, charge-passed method, and X-ray microscopy (XRM) test. The results consistently show that all types of nanoparticles tested in this paper can be successfully driven into the cement annulus within the wellbore system. The pressure (6.89 MPa) and temperature (80 °C) in the pressure vessel, and the surrounding rock can directly affect the injection effectiveness. The nanoparticle injection technology is proven to be beneficial to the cracked cement annulus for preventing the leakage of CO2 gas through the lab-scale wellbore system.